Adequacy of initiating TNF antagonists within 3 weeks of starting latent tuberculosis infection treatment in patients with immune-mediated inflammatory diseases. Issue 4 (2nd April 2016) - Yang, Ji-Young; Jo, Kyung-Wook; Hong, Seokchan; Yoo, Bin; Lee, Chang-Keun; Kim, Yong-Gil; Yang, Suk-Kyun; Byeon, Jeong-Sik; Kim, Kyung-Jo; Ye, Byong Duk; Park, Sang-Hyoung; Shim, Tae Sun
Abstract: Background This study investigated whether tumour necrosis factor (TNF) antagonists should be initiated within 3 weeks of latent tuberculosis infection (LTBI) treatment in patients with immune-mediated inflammatory disease (IMID).Methods Between June 2004 and October 2013, a total of 1521 IMID patients were screened for LTBI before initiating anti-TNF therapy at a tertiary referral centre in South Korea. Their medical records were retrospectively reviewed.Results A total of 411 patients received LTBI treatment before receiving TNF antagonists between June 2004 and October 2013. The mean age of the 411 study subjects was 44.5 years and 261 (63.5%) were male. Anti-TNF agent was initiated in 61 patients (14.8%) within 3 weeks after chemoprophylaxis for LTBI, but 3 weeks later in the remaining 350 patients (85.2%). These two groups were comparable in terms of baseline characteristics, but differed significantly in the mean duration of LTBI treatment before commencing anti-TNF therapy (8 vs 30 days, p  < 0.001). A total of six patients developed TB during the follow-up period and received anti-TNF agents 3 weeks after initiation of LTBI treatment. None of the patients who commenced TNF antagonist therapy within 3 weeks of LTBI treatment developed TB.Conclusions TNF antagonists may be initiated within 3 weeks of commencing LTBI treatment in IMID patients.